Healthy Teaching at the University Level, an Urgent Metamorphosis - Castillo-Cedeño, Ileana (2016)
This article belongs to an interdisciplinary process developed at the National University of Abstract. This article arises from the research process of the Healthy Pedagogy project at the Center for Research and Teaching in Education (CIDE, by its acronym in Spanish) of the National University of Costa Rica (UNA, by its acronym in Spanish). The Center is well known as the country’s teacher training school. CIDE is structured in 5 academic units or departments, that attend the undergraduate and postgraduate education at different levels of the education system. The research recovers the issue of health, as a crucial element of social and educational praxis. The Center relies on pedagogy as a science that supports the welfare of life in an holistic dimension. This is an interdisciplinary study that emerges from one of the objectives of the research project: identify healthy educational experiences in CIDE by applying a semi-structured questionnaire to 19 teachers from the 5 academic units. An integrated multimodal approach is used, quantitative and qualitative aspects are combined, because they offer an opportunity to explore, describe and contribute to the interpretation of what healthy means in light of the participants perceptions. The results suggest that there is a diversity of criteria regarding the meaning of healthy and how to generate appropiate personal and professional environments. This allows to identify the challenge, both for CIDE and the University, of approaching the health issue by articulating policies that promote healthy lifestyles inside and outside the classrooms in order to treat the educational community with social responsibility.